PENYULUHAN FISIOTERAPI KOMUNITAS TENTANG OSTEOARTHRITIS GENU KEPADA KELOMPOK PROLANIS DI PUSKESMAS KSATRIA - Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; Yosni Handayani Gea (Nusantara Hasana Journal, 2024)
The community physiotherapy outreach on genu osteoarthritis for PROLANIS participants at Ksatria Health Center aimed to increase knowledge, symptom understanding, and the ability to perform physiotherapy techniques at home through interactive lectures, demonstrations of quadriceps strengthening, stretching, and balance exercises, and a Q&A session; pre- and post-test evaluations indicated significant improvements in definitions, pathophysiology, clinical symptoms, and home-based practice skills, reinforcing the linkage between the health center services and chronic disease management under PROLANIS. Recommendations include routine mentoring, enhanced outreach facilities, ongoing training for health personnel, and the development of online educational modules for participants unable to attend.